5-Aminolaevulinic Acid (ALA) for the Fluorescence Detection of Bronchial Tumors. Issue 2 (1999) - Huber, Rudolf M.; Gamarra, F.; Hautmann, H.; Häußinger, K.; Wagner, S.; Castro, M.; Baumgartner, R.
Abstract : At the moment only early detection of lung cancer offers a good prognosis for the patients. Conventional white light endoscopy is mostly insufficient for early diagnosis. Therefore we developed a system of fluorescence diagnosis using 5-aminolaevulinic acid (ALA) exogeneously applied. As precursor of the heme synthesis it is metabolized to protoporphyrin IX – a red fluorescent substance. Therefore protoporphyrin IX accumulates in tumorous and premalignant tissue, and can be directly visualized by fluorescence bronchoscopy. Excitation with blue light (380–435 nm) causes a red fluorescence, which can be detected after filtering most of the blue component with the naked eye or a camera system. After earlier work with laser systems and cold light sources we now use the system D-Light AF for the fluorescence diagnosis using ALA-induced protoporphyrin IX fluorescence.